3 divided by 0.05 is equal to 60.
Given that we need to find the value of 3 divided by 0.05,
To calculate 3 divided by 0.05, you can use the following formula:
3 ÷ 0.05 = [tex]\frac{3}{0.05}[/tex]
To divide by a decimal number like 0.05, you can multiply both the numerator and denominator by a power of 10 to eliminate the decimal point.
In this case, multiplying by 100 will work:
[tex]3 \div 0.05 = \frac{3}{0.05} \times\frac{100}{100}[/tex]
Now we can perform the division:
[tex]3 \div 0.05 = \frac{3\times 100}{0.05 \times100}[/tex]
Simplifying further:
[tex]3 \div 100 =[/tex] [tex]\frac{300}{5}[/tex]
Finally, performing the division:
300 / 5 = 60
Therefore, 3 divided by 0.05 is equal to 60.
Learn more about division click;
https://brainly.com/question/2273245
#SPJ6
Which formula is used to calculate the standard deviation of sample data?
s = StartRoot StartFraction (x 1 minus x overbar) squared + (x 2 minus x overbar) squared + ellipsis + (x n minus x overbar) squared Over n minus 1 EndFraction EndRoot.
sigma squared = StartFraction (x 1 minus mu) squared + (x 2 minus mu) squared + ellipsis + (x N minus mu) squared Over N EndFraction
Sigma = StartRoot StartFraction (x 1 minus mu) squared + (x 2 minus mu) squared + ellipsis + (x N minus mu) squared Over N EndFraction EndRoot
x = StartFraction (x 1 minus x overbar) squared + (x 2 minus x overbar) squared + ellipsis + (x n minus x overbar) squared Over n minus 1 EndFraction
Answer:
the first one
Step-by-step explanation:
i just got it right on edge
The standard deviation of sample data is "[tex]s = \sqrt{\frac{(x_1 -\bar{x})^2+ (x_2-\bar{x})^2 + ..... + (x_n -\bar{x})^2}{ n- 1}}[/tex]"
The standard deviation of the sample data:Random variables, samples, statistical populations, information sets, or probabilistic distributions are equal to the square root of its variance.
It's much less resilient in reality than the average absolute deviation, but it makes algebraic expressions easier.
A sampling divided by the size of the data set is less than one, n - 1. To get the standard deviation, take the square root of the variance. The standard deviation is obtained by taking the square root of the standard deviation.
Therefore, the standard deviation of sample data is "[tex]s = \sqrt{\frac{(x_1 -\bar{x})^2+ (x_2-\bar{x})^2 + ..... + (x_n -\bar{x})^2}{ n- 1}}[/tex]"
Find out more information about the standard deviation here:
brainly.com/question/12402189
Hey help me out with my homework thank you. STAY SAFE.
Answer:
angle A = 166 degrees
Step-by-step explanation:
so first you have to look at the problem and see what type of relationship the angles have. so if you draw it out yourself, it makes it a little easier and you can see that the two angles are corresponding angles, which means theyre both congruent or, equal.
after you find that out you can set up an equation so,
7x + 40 = 3x + 112
you do the math...
4x + 40 = 112
4x = 72
x = 18
but you cant stop here, you have to plug in x to find teh entire angle A
7 (18) + 40 = ?
126 + 40
166
bam.
Describe the shape resulting from the cross section.
A.
parallelogram
C.
rectangle
B.
triangle
D.
circle
Answer:
Is this all of the info?
Step-by-step explanation:
Answer:
i am still confuse plz give more info
Step-by-step explanation:
PLS HELP I AM TIMED 10 POINTS You are told that a triangle has two equal angles. What type of triangle could it be? Check all of the boxes that apply. acute equilateral isosceles obtuse right scalene
Answer:
Obtuse, right, isoceles, acute
Step-by-step explanation:
Use a trigonometric ratio to find the value of x. Round your answer to the nearest
tenth.
Answer:
x = 7.6
Step-by-step explanation:
Label the values you have on the triangle: The X is opposite, the 33 is your theta (ø) and 14 is your hypotenuse
Plug these values into the equation sin(ø)=o/h making the equation sin(33)=x/14.
Take the 14 and multiply it on the opposite side, making the equation look like this: 14xsin(33)=x
Then plug this into the TI-83/84 calculator and make sure it is degree mode (mode, degree)
Then just round to the nearest tenth. :)
Translate the sentence into an equation.
Four times the sum of a number and 2 equals 5.
Use the variable x for the unknown number.
Simon is having a birthday party, and each guest gets a bag of party favors. Each goody bag contains one of 7 different toy cars and one of 3 different toy trucks. Each goody bag also has one of 4 different temporary tattoos. How many different combinations of party favors can there be in a goody bag?
Answer:
84
Step-by-step explanation:
7*3=21*4=84
7 toy cars multiplied by the combination of 3 toy trucks equals 21 then times that by the 4 temp. tattoos, then you get 84
1.The table represents a linear function. Find the values of a, b, and c. Show your work.
2.Write the equation for the line graphed below.
3.Layla and Sam are both dog sitters. Layla charges $2 per day plus a sign-up fee of $3. Sam charges a flat rate of $3 per day. The system of linear equations below represents y, the total amount earned in dollars for x days of dog sitting.
a)Write the equation to represent Layla’s fees.
b)Write the equation to represent Sam’s fees.
c)After how many days do Layla and Sam earn the same amount for dog sitting?
What is that amount?
PLEASE HELP
Answer:
1. a= 1
b=10
c=9
2.y=1/2x-1
3. a) y=3x + 0
b) y=2x+3
c)3
d) $9
Step-by-step explanation:
1. The values in the x-axis increase by 2 hence a=3-2=1 and c=7+2=9. For the y-values, they increase by 1.
2. The equation of the line can be written in the slope form of y=mx+c where m is the gradient of the line and c is the y-intercept
Taking points on the line ; (-2,-2) and (2,0) the gradient m is ;
m=Δy/Δx Δy=0--2=2 Δx=2--2=4 m=2/4⇒1/2
From the graph c= -1
The equation y=1/2x-1
3
(a) Equation representing Layla fees is;
Taking points (1,3) and (2,6) the gradients is
m=Δy/Δx (6-3)/(2-1) = 3/1 =3
Taking m=3, point (1,3) and (x,y) the equation will be;
m=Δy/Δx
3=y-3/x-1
3(x-1) = y-3
3x-3 = y-3
3x-3+3=y
y=3x + 0 ------equation for Layla line
(b) Equation representing Sam line for fees is
Taking points (1,5) and (2,7) where c=3
m=Δy/Δx
m=7-5/2-1
m=2/1 =2
Equation : y=2x+3
c) The point of intersection of the lines which is 3 days
d)The amount is $9
Solving equations and distributive property
Answer:
The answer is 10
Step-by-step explanation: You multiply the 2 times twenty to get 40 then multiply the 2 times 2x to get 4x then subtract fourty from both sides and you will get fourty and then divide so 40 divided by 4x equals 10.
Answer:
x=10
Step-by-step explanation:
2x20=40 and 2x2x=4x move the 40 to the other side so 80-40=40 so 4x=40 4x10=40 so 10 should be correct.
hope this helps!
The circumference of a circle is 18m. Find its diameter, in meters.
quick answers please
Answer:
5.72957795
Step-by-step explanation:
18/pi
Work out the size of angle x.
Answer:
x = 13°
Step-by-step explanation:
x = 180° - 85° - (180° - 98°)
= 180° - 85° - 82°
= 13°
Answer:
x = 13°
Step-by-step explanation:
x = 180° - 85° - (180° - 98°)
= 180° - 85° - 82°
= 13°
Richard went to the store to buy some pencils and 2 packs of paper. Perry who went with Richard to the store, spent $30 on a magazine and some candy bars. If the magazine cost $6 and each candy bar cost $3, then how many candy bars did Perry buy?
Answer:
8
Step-by-step explanation:
$30 - $6 for the magazine = $24 ÷ $3 for one candy bar = 8 candy bars
Answer:
8 candy bars
Step-by-step explanation:
6 + 3x = 30
3x = 24
x = 8
The system of equations(In attachment) has
A) One Solution
B) Infinitely Many Solutions
C) No Solutions
Answer:
4x - 6 = 4x + 4
-6 not equal to 4
Therefore, the answer is c
No Solutions
Step-by-step explanation:
PLS HELP! THIS IS OVERDUE! ''What is the range of possible lengths for the third side of a triangle that has side lengths of 7 and 10?''
The length has to be greater than the absolute difference between the other two lengths, but less than the sum of them. In other words, if your unknown side length is a, and the other two are b and c, then its |b - c| < a < b + c
So, putting in your values, you have 10 - 7 < a < 10 + 7, which is 3 < a < 17
So, your range is from 3 to 17 (non inclusive).
The length has to be greater than the difference between the named two lengths, but less than the sum of them. So 3-17 is your answer.
For the expression 6p^2+4p, if p=2, what would the expression be equal to? (p^2 is the same as p*p)
Answer:
[tex]32[/tex]
Step-by-step explanation:
6p^2+4p, if p=2
[tex]6(2) {}^{2} + 4(2) \\ = 6 \times 4 + 4 \times 2 \\ = 24 + 8 \\ = 32[/tex]
Factor the polynomial below.
χ2 – 5x - 14
(x-5)(x - 14)
- 14)(x + 1)
(x + 70x - 2)
(x+2)(x - 7).
Answer:
(x + 2)(x - 7)
Step-by-step explanation:
Given
x² - 5x - 14
Consider the factors of the constant term (- 14) which sum to give the coefficient of the x- term (- 5)
The factors are + 2 and - 7, since
2 × - 7 = - 14 and 2 - 7 = - 5, thus
x² - 5x - 14 = (x + 2)(x - 7)
What system of equations is shown on the graph below?
On a coordinate plane, a line goes through points (negative 2, 0) and (0, negative 4) and another line goes through (0, negative 2) and (4, 0).
x minus 2 y = negative 4 and 2 x + y = 4
x minus 2 y = 4 and 2 x + y = negative 4
x minus 2 y = negative 2 and 2 x + y = negative 4
x minus 2 y = 2 and 2 x + y = 4
Answer:
The equation of the line passing through the points (-2,0) and (0,-4)
[tex] \frac{y - y1}{x - x1} = \frac{y2 - y1}{x2 - x1} [/tex]
[tex] \frac{y - 0}{x - ( - 2)} = \frac{ - 4 - 0}{0 - ( - 2)} = \frac{ - 4}{2} = - 2[/tex]
[tex]y = - 2(x + 2) \\ y = - 2x - 4[/tex]
[tex]2x + y = - 4[/tex]
The equation of the line passing through the points (0,-2) and (4,0)
[tex]\frac{y - y1}{x - x1} = \frac{y2 - y1}{x2 - x1} \: [/tex]
[tex] \frac{y - ( - 2)}{x - 0} = \frac{0 - ( - 2)}{4 - 0} [/tex]
[tex] \frac{y + 2}{x} = \frac{1}{2} [/tex]
[tex]x - 2y = 4[/tex]
Option B
x minus 2 y = 4 and 2 x + y = negative 4
The system of equation can be determine by using formula of equation of the line passing through the points [tex](x_1, y_1)[/tex] and [tex](x_2, y_2)[/tex].
The system equation would be [tex]2x+y=-4[/tex] and [tex]x-2y=4[/tex].
Given:
The given points are [tex](-2,0)[/tex] and [tex](0,-4)[/tex] and for another line [tex](0,-2)[/tex] and [tex](4,0)[/tex].
Find the equation line passing through point [tex](-2,0)[/tex] and [tex](0,-4)[/tex] .
[tex]\dfrac{y-y_1}{x-x_1}=\dfrac{y_2-y_1}{x_2-x_1}[/tex]
Substitute the value in above equation.
[tex]\dfrac{y-0}{x-(-2)}=\dfrac{-4-0}{0-(-2)}\\y=-2(x+2)\\y=-x-4\\2x+y=-4[/tex]
Find the equation line passing through point [tex](0,-2)[/tex] and [tex](4,0)[/tex] .
[tex]\dfrac{y-y_1}{x-x_1}=\dfrac{y_2-y_1}{x_2-x_1}[/tex]
Substitute the value in above equation.
[tex]\dfrac{y-(-2)}{x-0}=\dfrac{0-(-2)}{4-0}\\\\x-2y=4[/tex]
Thus, the system equation would be [tex]2x+y=-4[/tex] and [tex]x-2y=4[/tex].
Learn more about equation of line here:
https://brainly.com/question/2564656
Tammy is buying a soft toy from a shop. The cost of the toy is 9 dollars and she also has to pay a sales tax that is 15% of the price of the toy. She wants to know the total cost she will have to pay.
Answer:10.35 dollars
Step-by-step explanation: 15% of 9 dollars is 1.35
so you add 1.35 to 9 dollars to find the total cost
The total cost she will have to pay for the toy is $10.35.
What is the percentage?A percentage is a figure or ratio that can be stated as a fraction of 100. If we need to calculate the percentage of a number, we must divide it by its full value and then multiply it by 100. As a result, the percentage is one part in one hundred. "Per 100" is short for "per percent." It is represented by the symbol "%".
Given the cost of the toy = $9
sale tax on toy = 15% of the total price
sale tax on toy = 15% of 9
sale tax on toy = 0.15 x 9
sale tax on toy = $1.35
total cost to pay = $9 + $1.35
total cost to pay = $10.35
Hence total cost to pay is $10.35.
Learn more about percent;
https://brainly.com/question/28840349
#SPJ5
What is true about the transformation that was
performed? Check all that apply
g(x) has an axis of symmetry atx=3
g(x) is shifted down 5 units from the graph of fix).
g(x) is shifted right 3 units from the graph of f(x).
g(x) is shifted up 4 units from the graph of f(x).
g(x) is narrower than fu).
Answer:
the answer is A C and D if you’re using edu.
Step-by-step explanation:
Answer:
A,C,DStep-by-step explanation:
PLEASE ANSWER THE RIGHT ANSWER PLEASE DO NOT GUESS. PS, ITS MORE THAN ONE ANSWER. :)
Which statements describe examples of how science and technology benefit society? Check all that apply.
A)The publication of a study confirms the existence of an earthquake fault line.
B)The creation of new oil fracking methods reduces gasoline costs at the pump.
C)The invention of Bluetooth encourages automakers to create hands-free devices.
D)Concerns about health effects from smog are monitored by well-established methods.
E)Emissions of greenhouse gases promote innovative ideas to monitor environmental effects.
Answer:
B C D E
Step-by-step explanation:
B) The creation of new oil fracking methods reduces gasoline costs at the pump.
C) The invention of Bluetooth encourages automakers to create hands-free devices.
D) Concerns about health effects from smog are monitored by well-established methods.
E) Emissions of greenhouse gases promote innovative ideas to monitor environmental
Tom deposits $300 into an account that pays simple interest at a rate of 4% per year. How much interest will he be paid in the first 6 years?
Answer:
22.90 is the answer i can't write somet
use my computer has problems
I = P*r*t = 800*0.06*2 =
Find the common difference: 29, 21, 13, 5, ...
Find
Answer:
8
Step-by-step explanation:
Answer:
7
Step-by-step explanation:
subtract diffrences
which graph represents a system of equations with one solution
The graph shows the system of equation has ''No solution.''
What is Equation of line?The equation of line in point-slope form passing through the points
(x₁ , y₁) and (x₂, y₂) with slope m is defined as;
⇒ y - y₁ = m (x - x₁)
Where, m = (y₂ - y₁) / (x₂ - x₁)
Given that;
The graph of a system of equation shown in figure.
Now, We have;
The graph of system of equation has two parallel lines.
Hence, The graph shows the system of equation has No solution.
Thus, The graph shows the system of equation has ''No solution.''
Learn more about the equation of line visit:
https://brainly.com/question/18831322
#SPJ2
Adrian cuts a block of wood as shown. What is the volume of the block of wood?
Answer:
432
Step-by-step explanation:
Volume of cuboid:
12 x 4.5 x 5.5 = 297
volume of traingular prism:
(12x5)/2 x 4.5 =135
add them together:
135+297 =432
hope this helps!
So, the required volume of the given wooden block is 432 cubic cm.
The volume of the rectangular and triangular prism:The formula for the volume of the rectangular prism is,
[tex]v=l\times b \times h[/tex]
And the formula for the volume of the triangular prism is,
[tex]v=\frac{1}{2} \times b \times h[/tex]
It is given that,
The volume of the wood is equal to the volume of the rectangular prism and triangular prism.
So, by using the above formula we can write as,
The volume of the wood is,
= volume of the wood is equal to the volume of the rectangular prism + triangular prism.
[tex]=l\times b\times h+\frac{1}{2}\times h\times l\\ =12\times 4.5 \times 5.5 +\frac{1}{2} \times 12\times 4.5 \times 5\\=297+135\\=432 cm^3[/tex]
Learn more about the topic volume of the rectangular and triangular prism:
https://brainly.com/question/16354624
Which of the following is the best reason that it might be difficult to predict an individual's future health issues?
a Health issues are determined by environmental factors, which are subject to change.
b. Health issues are determined by a complex interaction of environmental and genetic factors, which is
difficult to predict
C. Health issues are determined by genetic inheritance, which is not fully understood.
d Health issues depend on lifestyle choices, which are not always predictable.
Answer:
b
Step-by-step explanation:
Answer:
b.
Step-by-step explanation:
Health issues are determined by a complex interaction of environmental and genetic factors, which is difficult to predict.
If the terminal ray of β lies in the fourth quadrant and sin (β) = -√3/3 determine cos(β) in simplest form.
Answer:
[tex]cos(\beta)=\frac{\sqrt{6}}{3}}[/tex]
Step-by-step explanation:
we know that
If the terminal ray of β lies in the fourth quadrant
then
sin (β) is negative and cos (β) is positive
Remember the trigonometric identity
[tex]sin^2(\beta)+cos^2(\beta)=1[/tex]
we have
[tex]sin(\beta)=-\frac{\sqrt{3}}{3}[/tex]
substitute
[tex](-\frac{\sqrt{3}}{3})^2+cos^2(\beta)=1[/tex]
[tex]\frac{3}{9}+cos^2(\beta)=1[/tex]
[tex]cos^2(\beta)=1-\frac{3}{9}[/tex]
[tex]cos^2(\beta)=\frac{6}{9}[/tex]
apply root square both sides
[tex]cos(\beta)=\frac{\sqrt{6}}{3}}[/tex]
Find the radius circumference =62.8mi
Answer:
r = 10
Step-by-step explanation:
C = 62.8 = 2π·r
62.8 = 2·3.14·r
r = 62.8/2·3.14
= 31.4/3.14
= 10
Answer:
10 miles
Step-by-step explanation:
The circumference of a circle can be found using:
[tex]c=2r\pi[/tex]
We know circumference is 62.8, so we can substitute it in
62.8=[tex]2r\pi[/tex]
We want to find r, so we have to isolate it.
Divide both sides by [tex]2\pi[/tex] or 2*3.14 which is 6.28
62.8=[tex]2r\pi[/tex]
62.8=6.28r
62.8/6.28=6.28r/6.28
r=10
So, the radius is 10 miles
Make a the subject of:
v = u + at
Answer:
[tex]a = \frac{v - u}{t} \: [/tex]
Step-by-step explanation:
[tex]v = u + at[/tex]
[tex]at = v - u[/tex]
[tex]a = \frac{v - u}{t} [/tex]
In the circle below, UW is a diameter and UX is tangent at U. Suppose m UV=128
Answer:
Step-by-step explanation:
The value of the angle ∠VUW is 26° and ∠VUX will be 116°.
What is a circle?A circle is a geometrical figure which becomes by plotting a point around a fixed point by keeping a constant distance.
In our daily life, we always see circular objects for example our bike wheel.
The longest line which can be drawn inside the circle will be the diameter.
Area of circle = πr² and the perimeter of circle = 2πr where r is the radius of the circle.
Given the circle
Since ∠UOV is 128°
So,
∠UOW = 180 - ∠UOV
∠UOW = 180 - 128 = 52°
Now,
∠VUW = 1/2 ∠UOW
∠VUW = (1/2)52 = 26°
Now ∠VUX = ∠VUW + 90°
∠VUX = 26 + 90 = 116°
Hence "The value of the angle ∠VUW is 26° and ∠VUX will be 116°".
To learn more about the circle,
https://brainly.com/question/266951
#SPJ2
a(1 ) = -2 a(n) = a(n - 1) - 5 Find the 4 ^ (th) term in the sequence .
Answer:
-17
Step-by-step explanation:
Each term in the sequence is 5 less than the one before, so the first 4 terms are ...
-2, -7, -12, -17
The 4th term of the sequence is -17.
__
The general term (an) of the sequence can be written as ...
an = a1 +d(n -1)
where a1 is the first term and d is the common difference. Here, those are ...
a1 = -2, d = -5
so the general term is ...
an = -2 -5(n -1)
We can use this to find the 4th term:
a4 = -2 -5(4 -3)
a4 = -17